2010
DOI: 10.1128/aem.02945-09
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Topology of Outer Membrane Protein AlgE, Which Is Required for Alginate Production in Pseudomonas aeruginosa

Abstract: The ubiquitous opportunistic human pathogen Pseudomonas aeruginosa secretes a viscous extracellular polysaccharide, called alginate, as a virulence factor during chronic infection of patients with cystic fibrosis. In the present study, it was demonstrated that the outer membrane protein AlgE is required for the production of alginate in P. aeruginosa. An isogenic marker-free algE deletion mutant was constructed. This strain was incapable of producing alginate but did secrete alginate degradation products, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…AlgE forms a monomeric 18-stranded antiparallel β-barrel with the register of the β-strands being in reasonable agreement with previously reported topology models (20,23) (Fig. S1).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…AlgE forms a monomeric 18-stranded antiparallel β-barrel with the register of the β-strands being in reasonable agreement with previously reported topology models (20,23) (Fig. S1).…”
Section: Resultssupporting
confidence: 78%
“…As reported previously, the algE mutant was nonmucoid and produced no detectable levels of alginate (Fig. 4C) (23). When the algE gene was introduced on a plasmid, wild-type levels of alginate production were restored.…”
Section: Resultsmentioning
confidence: 51%
“…1). Hay et al have previously demonstrated that insertion of this epitope in loop 6 does not affect alginate production in P. aeruginosa (19). Using this approach, we investigated the correlation between the number of factories and alginate production level, their dependence on the production of alginate precursor, and the spatial distribution pattern of alginate factories on the cell surface.…”
mentioning
confidence: 99%
“…According to these findings, AlgX plays a crucial role in the localization of the porin AlgE (21). The absence of any of the scaffold proteins AlgG, AlgX, AlgK, or AlgE in a complex leads to release of alginate in the periplasm, where it is degraded by AlgL, resulting in a lower polymer yield (1,(16)(17)(18)(19)(20)24).…”
mentioning
confidence: 99%
See 1 more Smart Citation